Pengaruh Kemiskinan dan Kesehatan terhadap Indeks Pembangunan Manusia di Daerah Provinsi Jawa Barat - Navia Istiqomah; Rini Agustin Muda; Putri Indriyani; Misfi Laili Rohmi (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
The Human Development Index (HDI) is a key indicator that reflects the quality of life of society, including the dimensions of health, education and income. This research aims to analyze the influence of poverty and health on HDI in West Java Province. Poverty, as an economic factor, and health, as a social factor, interact with each other and influence the level of the Human Development Index. In this research, we used secondary data obtained from the West Java Central Statistics Agency, with a quantitative approach through multiple regression analysis. The research results show that the poverty variable has a significant negative impact on HDI, while the health variable shows a significant positive impact on HDI.